Pengembangan Media Edukasi Game Tastarok Tingkat Dasar untuk Meningkatkan Perilaku Pencegahan Merokok Anak - Mujito Mujito; Andi Hayyun Abiddin; Mohamad Miftachul Ulum (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Background: The promotion of non-smoking behavior in elementary schools is one form of promotion of healthy behavior. Aims: Produce educational media that we're able to stimulate smoking prevention behavior in school-age children. Methods: Research and Development design was used with ADDIE development procedures. The subjects consisted of 15 groups of trial respondents and 20 groups of research respondents, from school-age children in Sananwetan State Primary School 3, Blitar City. The object under study was the quality and effectiveness of the basic level of Tastarok game education media. Retrieval of data was done by interview techniques, questionnaires, and checklists, to measure aspects of the feasibility of the material, graphic engineering, and media effectiveness. Results: The product validation results were declared very feasible to be used as a health promotion media as evidenced by the results of the paired t-test analysis with p=0.000, which means there is a significant difference between the average beliefs in smoking prevention behavior before and after the intervention. Conclusion: Educational media for elementary level tastarok games can improve smoking prevention behavior in children, so health promotion workers are expected to be able to use this educational media in health promotion in schools.